2021
DOI: 10.1101/2021.06.15.448553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergent properties of coupled bistable switches

Abstract: Understanding the dynamical hallmarks of network motifs is one of the fundamental aspects of systems biology. Positive feedback loops constituting one or two nodes, self-activation, toggle switch, and double activation loops, are commonly observed motifs in regulatory networks underlying cell-fate decision systems. Their individual dynamics are well-studied; they are capable of exhibiting bistability. However, studies across various biological systems suggest that such positive feedback loops are interconnecte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Third, it is still challenging to evaluate motif coupling, i.e., how one circuit motif interacts with another to produce the desired behaviors. The coupling of circuit motifs has been shown to play important roles to the overall behavior of gene circuits 21,22 . In particular, the role of circuit coupling may depend on the proportion of shared nodes between the two coupled circuit motifs 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, it is still challenging to evaluate motif coupling, i.e., how one circuit motif interacts with another to produce the desired behaviors. The coupling of circuit motifs has been shown to play important roles to the overall behavior of gene circuits 21,22 . In particular, the role of circuit coupling may depend on the proportion of shared nodes between the two coupled circuit motifs 5 .…”
Section: Introductionmentioning
confidence: 99%
“…To model the dynamical behaviors of all these circuits in a high throughput way, we applied our recently developed method, random circuit perturbation (RACIPE) 24 , to simulate an ensemble of ODE models with randomly generated kinetic parameters and analyze the steady- state gene expression distribution from these models. RACIPE has been applied to elucidate the dynamics of synthetic gene circuits 10, 21, 25 , gene networks regulating stem cell differentiation 26 , cell cycle 27 , B-cell development 28 , and epithelial-mesenchymal transitions 29, 30 (EMT). These previous studies have shown that, despite having randomly sampled kinetic parameters and initial conditions, steady state solutions of models generally converge to distinct clusters of gene expression patterns representing the functional states of the circuit.…”
Section: Introductionmentioning
confidence: 99%
“…The coupling of circuit motifs has been shown to play important roles in the overall behavior of gene circuits. 21 , 22 In particular, the role of circuit coupling may depend on the proportion of shared nodes between the two coupled circuit motifs. 5 Another recent study 23 developed a framework to identify over-represented connections of circuit motifs, termed hypermotifs, in existing biological, neuronal, social, linguistic, and electronic networks.…”
Section: Introductionmentioning
confidence: 99%
“…To model the dynamical behaviors of all these circuits in a high throughput way, we applied our recently developed method, random circuit perturbation (RACIPE), 25 to simulate an ensemble of ODE models with randomly generated kinetic parameters and analyze the steady-state gene expression distribution from these models. RACIPE has been applied to elucidate the dynamics of synthetic gene circuits, 10 , 21 , 26 gene networks regulating stem cell differentiation, 27 cell cycle, 28 B-cell development, 29 and epithelial-mesenchymal transitions 30 , 31 (EMTs). These previous studies have shown that despite having randomly sampled kinetic parameters and initial conditions steady state solutions of models generally converge to distinct clusters of gene expression patterns representing the functional states of the circuit.…”
Section: Introductionmentioning
confidence: 99%
“…While all three of these motifs can give rise to multistability, the presence of these motifs themselves is not sufficient for multistability. The appropriate sets of parameters that govern various interactions among these motifs are crucial for the emergence of multistability (32,7,27) . Furthermore, the noisy nature of biological systems can alter the likelihood of achieving multistability using these motifs (33,34,53) .…”
Section: Introductionmentioning
confidence: 99%